Smart wound dressing for infection monitoring and NIR-triggered antibacterial treatment. (23rd January 2020) - Qiao, Bianbian; Pang, Qian; Yuan, Peiqi; Luo, Yilun; Ma, Lie
Abstract : Hydrogel-based wound dressings can monitor infection via pH-responsive FRET changes and provide on-demand antibacterial treatment via NIR-triggered antibiotic release. Abstract : Wound infection is a major challenge in the clinic that greatly hinders the wound healing process. It is highly important to develop smart wound dressings that can sense bacterial infection at early stages and provide on-demand treatment. In this work, a smart hydrogel-based wound dressing capable of monitoring bacterial infection via a pH-responsive fluorescence resonance energy transfer (FRET) transition of Cyanine3 (Cy3) and Cyanine5 (Cy5) in a bacterial environment and providing on-demand treatment of infection via near infrared (NIR) light-triggered antibiotic release was developed. The smart hydrogel was prepared by physical crosslinking of polyvinyl alcohol (PVA) and an ultraviolet (UV)-cleavable polyprodrug (GS-Linker-MPEG), in which Cy3 and Cy5-modified silica nanoparticles (SNP-Cy3/Cy5) were loaded and acted as a pH-responsive fluorescent probe to detect bacterial infection based on the FRET effect between Cy3 and Cy5. Also, up-conversion nanoparticles (UCNP) were loaded into the hydrogels to cleave the UV-responsive GS-Linker-MPEG and achieve NIR-responsive release of GS in the bacterial environment. The in vitro studies proved that the smart hydrogels present good water absorption ability and excellent mechanical properties as well as good biocompatibility, which are necessary for their application in wound dressings. Moreover, the hydrogels showed obvious FRET transitions in both acidic buffer and bacteria solution. Upon irradiating the hydrogels with NIR light, UCNP were able to convert NIR light to UV light to trigger the release of GS from the hydrogels for antibacterial treatment. This research is expected to provide a new strategy for self-reporting and effective treatment of wound infection.